Reactivity of aminophosphonic acids. Oxidative dephosphonylation of 1-aminoalkylphosphonic acids by aqueous halogens12. Issue 5 (3rd December 2015) - Drabowicz, Józef; Jordan, Frank; Kudzin, Marcin H.; Kudzin, Zbigniew H.; Stevens, Christian V.; Urbaniak, Paweł
Abstract : The quantitative halogen-promoted dephosphonylation of AA P occurs via pentacoordinate phosphorus derivative3 with the formation of phosphoric acid, carbonyls and nitrogen. Abstract : The reactions of 1-aminoalkylphosphonic acids with bromine–water, chlorine–water and iodine–water were investigated. The formation of phosphoric(v ) acid, as a result of a halogen-promoted cleavage of the Cα –P bond, accompanied by nitrogen release, was observed. The dephosphonylation of 1-aminoalkylphosphonic acids was found to occur quantitatively. In the reactions of 1-aminoalkylphosphonic acids with other halogen–water reagents investigated by 31 P NMR, scission of the Cα –P bond was also observed, the reaction rates being comparable for bromine and chlorine, but much slower for iodine.